Characteristic of immunophenotypes of normal endometrial, eutopic and ectopic endometrial tissue in women with endometriosis and infertility. - Medvedev, M. V.; Spon’ka, I. S.; Altanets, O. M.; Skoryk, V. R. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Endometriosis is considered as one of the most common causes of infertility in women. Despite the numerous published data on this subject, early stage diagnosis remains very low. Histologically normal endometriosis does not differ from the eutopic endometrium, so the search for features is transferred to the molecular level. Objective. Assess immunohistochemical markers ER, PGR, Ki-67, BCL-2, MMP-9 in normal endometrial, eutopic and ectopic endometrial tissue in women with endometriosis and infertility. Methods. 3 groups were divided according to expression of investigated marker in glands (ER, PGR, Ki-67, BCL-2, MMP-9) and stroma (ER, PGR, Ki-67). The strict included/excluded options (clinical and/or morphological) were used for organizing these groups. Rating staining immunohistochemical markers was conducted in at least 10 fields of view. Statistical processing of the data included nonparametric tests. Results. The statistical difference between normal endometrium and both eutopic and ectopic endometrium was established for markers ER, PGR, MMP-9; between normal and eutopic endometrium was set for markers BCL-2, Ki-67 (p <0.05 on all of characteristics). No case was there with statistical difference between eutopic and ectopic endometrium. Conclusion. For the diagnosis of endometriosis with women with infertility the complex of immunohistochemical markers ER, PGR, MMP-9 can be useful and also BCL-2, Ki-67 could be added as ability for improving an accuracy of suggested method.